Jovens e conselho de classe : um estudo de caso a partir da dimensão participativa no ensino médio integrado no IFRS - Campus Bento Gonçalves - Molon, Lilian Carla (My University, 2025)
This research is linked to the History and Philosophy of Education research line of the Graduate Program in Education at the University of Caxias do Sul. Its theme is one of the school's daily assessment practices: the class council in Integrated High School (EMI). The class council is a space for reflection on the pedagogical process and, therefore, a formative and dialogical assessment moment. The general objective was to investigate how students' participation in the class council is constituted, in order to understand what meanings are attributed to it. The investigative path is outlined in the qualitative approach and requires that the lenses consider the research object based on a case study at the Bento Gonçalves Campus of the Federal Institute, as a space for the reverberation of student narratives. The construction of empirical data was mobilized by the adoption of the following instruments: online questionnaire, collective interview and focus group. The empirical corpus consists of young students enrolled (1st to 3rd year) in technical courses integrated into High School at the Bento Gonçalves Campus, aged between 15 and 19 years old. The resulting narratives were analyzed under the prism of discursive textual analysis (DTA) by Moraes and Galiazzi (2011). The theoretical contribution is mainly constituted by Dalben (1995, 2004), Rocha (1986), Hoffmann (2017), Luckesi (2001 and 2023), Vasconcellos (2003), Stecanela (2009, 2010, 2012 and 2016), Paro (2000, 2020, 2022), Lück (2010), Gohn (2011), Freire (1996), Dayrell and Carrano (2014) and Pais (2003). The research findings indicate that the class council, as experienced and perceived by EMI students, is one of the few spaces for dialogue about the pedagogical process at the Bento Gonçalves Campus. On the other hand, the participation of class representatives and vice representatives in the class council highlights them, where students occupy the stage by imposition, assuming the role of passive messengers, while the audience ? the staff ? acts as judges; all of this in a distant and hierarchical manner: the students on one side, the staff on the other. The students believe that the council could develop in other ways, such as, for example, through a discussion circle; or through a genuine face-to face conversation committed to teaching and learning, where relationships are strengthened through open dialogue and legitimate listening; a space where students truly have the possibility of constructing a more meaningful and formative assessment. It is important that the institution reflect on the intentions of student participation in the class council, in order to also consider which assessment process should permeate the pedagogical process. [resumo fornecido pelo autor]
Está pesquisa está vinculada à linha de pesquisa História e Filosofia da Educação do Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul. Tem como tema uma das práticas avaliativas cotidianas da escola: o conselho de classe no Ensino Médio Integrado (EMI). O conselho de classe é um espaço de reflexão acerca do processo pedagógico e, por isso, um momento avaliativo formativo e dialógico. O objetivo geral foi o de investigar como se constitui a participação dos estudantes no conselho de classe, a fim de conhecer quais sentidos lhe são atribuídos. O percurso investigativo está delineado na abordagem qualitativa e exige que as lentes considerem o objeto de pesquisa a partir de um estudo de caso no Campus Bento Gonçalves do Instituto Federal, enquanto espaço de reverberação das narrativas estudantis. A construção dos dados empíricos foi mobilizada pela adoção dos seguintes instrumentos: questionário online, entrevista coletiva e grupo focal. O corpus empírico é constituído por jovens estudantes matriculados (1º ao 3º ano) nos cursos técnicos integrados ao Ensino Médio do Campus Bento Gonçalves, com idades entre 15 e 19 anos. As narrativas decorrentes foram analisadas sob o prisma da análise textual discursiva (ATD) de Moraes e Galiazzi (2011). O aporte teórico é constituído principalmente por Dalben (1995, 2004), Rocha (1986), Hoffmann (2017), Luckesi (2001 e 2023), Vasconcellos (2003), Stecanela (2009, 2010, 2012 e 2016), Paro (2000, 2020, 2022), Lück (2010), Gohn (2011), Freire (1996), Dayrell e Carrano (2014) e Pais (2003). Os achados da pesquisa indicam que o conselho de classe vivido e percebido pelos estudantes do EMI, figura como um dos poucos espaços de diálogo acerca do processo pedagógico no Campus Bento Gonçalves. Por outro lado, a participação dos representantes e vice-representantes de turma no conselho de classe os coloca em evidência, onde os estudantes ocupam o palco por imposição, assumindo o papel de mensageiros passivos, enquanto a plateia - os servidores, colocam-se como juízes; tudo isso de forma distante e hierarquizada: os estudantes de um lado, os servidores do outro. Os estudantes acreditam que o conselho poderia se desenvolver de outras maneiras, como, por exemplo, a partir de uma roda de conversa; ou de uma conversa cara a cara verdadeira e comprometida com o ensino e com a aprendizagem, onde as relações se fortalecem a partir de um diálogo aberto e de uma escuta legítima; um espaço onde os estudantes tenham verdadeiramente a possibilidade de construir uma avaliação mais significativa e formativa. É importante que a instituição possa refletir acerca das intencionalidades da participação estudantil no conselho de classe, para pensar, também, que processo avaliativo deve permear o processo pedagógico. [resumo fornecido pelo autor]
Keywords: Estudantes - Avaliação; Estudantes do ensino médio; Ensino médio; Jovens; Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul - Bento Gonçalves (RS); Students - Rating of; High school students; High school; Young adults; Federal Institute of Education, Science and Technology of Rio Grande do Sul - Bento Gonçalves (Brazil)